Fundamental Analysis and Stock Valuation for Investment Decisions : (Case Study of Companies Listed on the Sri Kehati Index for the 2020-2024 Period) - Nurman; Amiruddin Tawe; Indri Iswardhani; Ridwan Andi Mattoliang; Fakhirah Husain (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the fundamental condition and assess the investment feasibility of eleven issuers that consistently appeared in the Sri Kehati Index during the 2020–2024 period. Fundamental analysis was conducted using the financial ratios TATO, ROE, EPS, CR, DER, and DPR. The results show that UNVR and KLBF demonstrated high efficiency in asset management, while BBCA and BMRI exhibited strong profitability. JSMR had an aggressive capital structure but was supported by adequate liquidity. Meanwhile, UNVR and BBRI stood out for their generous dividend distribution policies. Stock valuation was carried out using two approaches: PER and PBV. Based on PER, nine issuers were classified as undervalued because their intrinsic values exceeded market prices, while two issuers (DSNG and SMGR) were considered overvalued. In contrast, the PBV approach indicated that ten issuers were overvalued, with only DSNG being undervalued. These differing results suggest that PER focuses more on a company’s earnings performance, whereas PBV emphasizes its book value. Therefore, stock investment assessment should be carried out comprehensively by considering more than one valuation method.